Investigating the Relationship between Socioeconomic Status and Traffic Behaviors of Pedestrians in Marand - Sepideh Harzand-Jadidi; Abolfazl Rahimi Bonab; Morteza Haghighi; Mohammad Saadati; Saeid Mousavi (Taṣvīr-i salāmat)
Background. Considering the high number of pedestrian accidents in Marand and their subsequent physical, psychological, social, and economic damages on the individual, family, and society, the current study was conducted to investigate the relationship between the socioeconomic status and traffic behavior of pedestrians. Methods. This descriptive-analytical study was conducted in Marand, one of the major cities in East Azerbaijan province of Iran in 2018-2019. The statistical population of the research included all the pedestrians of Marand. The statistical sample consisted of 515 pedestrians who were chosen from individuals who walked to the health centers. Data was collected using the pedestrian behavior questionnaire and the socioeconomic status questionnaire. Data analysis was conducted using SPSS software (version 23), which included descriptive statistics, independent t-test, and one-way analysis of variance (ANOVA). Results. The mean (standard deviation) of the total score of pedestrian traffic behavior in this study was 82.07 (7.80). The results of the independent t-test showed that the average score of aggressive behavior had a significant relationship with gender. As such, men had better traffic behaviors than women pedestrians. Based on the results of one-way ANOVA, the mean score of positive behaviors was significantly different in various age groups. Married pedestrians had fewer distracted behaviors than single pedestrians. Also, in all dimensions of traffic behavior, with the improvement of the socioeconomic status, the average score of traffic behavior increased. However, this increase was significant only in the subscales of adherence to traffic rules, positive behaviors, and distraction. Conclusion. According to the results of this study, pedestrians who had a lower socioeconomic status showed more unsafe behaviors while crossing the road. Also, unsafe behaviors were more common among female pedestrians and young age groups. Therefore, measures such as implementing educational and environmental interventions considering pedestrians’ demographic characteristics should be adopted to improve their traffic knowledge and behavior.